Indigenous and Crown Sovereignty in Canada - McNeil, Kent (Osgoode Digital Commons, 2019)
Peter Russell, a prominent Canadian political scientist, tells of the time he met with Dene leaders on his first visit to the Northwest Territories in 1974. A Dene woman opened the discussion by asking: “Professor Russell, I have two questions for you: What is sovereignty? And how did the Queen get it over us?” Years later, he described his response: “For the first question, I had a nice, pat answer based on Bodin, Hobbes, and my understanding of European international law. But I stumbled over the second. The truth of the matter is that I didn’t have a clue how Queen Victoria and her Canadian henchmen had ‘got sovereignty’ over the Dene.” Later, he said he “came to know that the right answer to the Dene woman’s second question was – in a word – ‘trickery.’ Or, to use the more ironic concept I learned from an Australian Aboriginal friend, it was ‘the white man’s legal magic’ that did the trick.”